Original paperAnalysis of the correlation between anxiety, depression, intensity of dyspnoea and severity of the bronchial asthma disease process - Pietras, Tadeusz; Panek, Michał; Witusik, Andrzej; Wujcik, Radosław; Szemraj, Janusz; Górski, Paweł; Kuna, Piotr (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Introduction : Bronchial asthma is a serious health problem worldwide. The prevalence of asthma is still high and patients represent a wide range of age and socio-economic status. Despite progress in diagnostic and therapeutic options, several studies have shown that asthma has an impact on health-related quality of life, length of hospitalization, prognosis and patients’ coping. Obturative disorders are associated with considerable emotional burden of the patient, which may result in the development of mood disturbances and anxiety disorders. Research more often than before emphasizes the clear role of psychopathological factors in the course of bronchial asthma. Aim : To assess the correlation between subjective and objective obstruction symptoms and the intensity of anxiety as a condition, and to estimate the intensity of anxiety and depression in patients suffering from bronchial asthma. Material and methods : The study enrolled 140 patients diagnosed with bronchial asthma and 100 healthy people, as a control group. Structured anamnesis was obtained and spirometry was performed in compliance with the standards set by the Polish Society of Lung Disease. Disturbances of ventilation and their severity were estimated according to the GINA Report. All the patients were assessed using the Beck Depression Inventory and the Spielberger State-Trait Anxiety Inventory (STAI). The subjective dyspnoea levels were estimated with the Borg scale. Results and conclusions : Multiple positive correlations were found between psychopathological factors and bronchial asthma patients versus the control group. Depression and dyspnoea modified the level of asthma severity according to GINA, grade of asthma control test and sensitivity to asthma treatment by ATS. A positive correlation was found between the declared dyspnoea level and the intensity of depression (p < 0.05) as well as the intensity of using inhaled and oral glucocorticosteroids (GCS) (p < 0.05) and inhaled short-acting beta agonist (SABA) and long-acting beta agonist (LABA) (p < 0.05). Anxiety-state, anxiety-trait and depression modified the feeling of dyspnoea (p < 0.001). Depression and dyspnoea determined pulmonary function test results (FEV1, FVC, FEV1%FVC). A positive correlation between psychopathological variables was observed in the study group of patients with bronchial asthma versus the control group.